Association Between Patient-Reported Pain and Remission or Low Disease Activity in Patients with Rheumatoid Arthritis: Data from RA-BE-REAL Prospective Observational Study - Peter C. Taylor; Walid Fakhouri; Samuel Ogwu; Ewa Haladyj; Inmaculada de la Torre; Bruno Fautrel; Rieke Alten; Peter Nash; Eugen Feist (Rheumatology and Therapy)
Abstract Introduction We aim to assess the association of patient-reported pain and remission or low disease activity (LDA) at 3 months (M) in patients receiving baricitinib or other treatments in RA-BE-REAL. Methods RA-BE-REAL reports on patients with rheumatoid arthritis (RA) who were prescribed, for the first time, baricitinib (cohort A) or a tumour necrosis factor inhibitor (TNFi) (cohort B-TNFi) or any other mode of action (OMA) (cohort B-OMA). Pain was measured using the visual analogue scale (VAS) (0–100 mm) and clinically meaningful pain improvement thresholds of ≥ 30%, ≥ 50% and ≥ 70% from baseline to 3, 6, 12 and 24 M. Results At 3 M, the mean change from baseline (CFB) pain VAS of patients in remission/LDA was − 32.6 mm (cohort A), − 27.3 mm (cohort B-TNFi) and − 28.0 mm (cohort B-OMA). Almost half the patients who were in remission/LDA receiving baricitinib achieved ≥ 70% pain relief. At 3 M, the proportion of patients in remission/LDA with pain VAS ≤ 20 mm was 62.1% (cohort A), 55.0% (cohort B-TNFi) and 55.6% (cohort B-OMA), while for those not in remission/LDA, it was 8.5% and 8.7% (cohort A and B-TNFi, respectively) and 5.3% (B-OMA). More patients on baricitinib achieved pain improvement in all analyzed thresholds than patients in cohort B-TNFi and B-OMA at 3 M. At 24 M, − 26.2 mm (cohort A), − 20.8 mm (cohort B-TNFi) and − 16.0 mm (cohort B-OMA) mean CFBs in pain measurement were observed. For baricitinib and the other treatments, residual pain decreased with achievement of remission/LDA and was sustained up to 24 M. Conclusions Patients in remission/LDA receiving baricitinib are more likely to achieve pain control than patients receiving TNFi/OMA.